A retrospective study of post-operative complications and cost analysis in robotic rectal resection versus laparoscopic rectal resection - Ali, Muhammad; Zhu, Xiaodong; Wang, Yang; Ding, Jianyue; Zhang, Qi; Sun, Qiannan; Baral, Shantanu; Wang, Daorong (Frontiers in Surgery, 2022)
Background: Robotic rectal cancer surgery has proven to be a viable alternative to laparoscopic surgery in treating rectal cancer. This study assessed the short-term operative measures of robotic versus laparoscopic surgery. Material: Data was obtained retrospectively from July 2019 to November 2021. Patient demographics, pre-and post-operative features, initial bowel movement, length of hospital stay, and short-term postoperative outcomes such as harvested lymph node, sepsis, Clavien-Dindo Classification, and cost were evaluated. Results: A total of 155 patients were treated for colorectal cancer, with 64 receiving robotic surgery and 91 receiving laparoscopic surgery. According to the Clavien-Dindo classification, there is a significant P < 0.05 between robotic and laparoscopic rectal surgery, with robotic having fewer patients in grade III-IV than laparoscopic. Despite this, laparoscopic surgery is associated with more sepsis patients (P<0.05), and harvested lymph nodes are likewise associated with significant results. Conclusion: With respect to post-operative complication and cost analysis, our finding imply that robotic rectal resection achieves better-quality short-term outcome but more costly than laparoscopic as well as Clavien-Dindo classification plays a crucial role in assessing postoperative rectal cancer complications and considerably impacts the quality of life.